Kajian Geografis Potensi Wilayah Berbasis Geospasial Kabupaten Pringsewu - Miswar, Dedy; Sugiyanta, I Gede; Yarmaidi, Yarmaidi (LaGeografia, 2020)
Regional potential is the ability of an area in the form of resources that can be used, exploited, and taken advantage of for further development so that it can improve and create regional capabilities. This study aims to make the potential of the physical region contained in the Geospatial based Pringsewu Regency, and the potential of the social area contained in the Geospatial based Pringsewu Regency. The method used is descriptive with a spatial approach. The results of the study are physical and social spatial data of the region including: administration, rainfall, groundwater basins, rivers and watersheds, landforms, slope, soil type, contour and height lines, land use, road networks, land capability, landslides, floods , population, and population density, so that it can be used as a reference in regional development planning.Â